Agricultural extension and advisory services in Nigeria, Malawi, South Africa, Uganda, and Kenya - Agwu, Ekwe Agwu; Suvedi, Murari; Chanza, Charity; Davis, Kristin E.; Oywaya-Nkurumwa, Anges; Mangheni, Margaret Najjingo (Michigan State University Press, 2023)
Agricultural extension and advisory services is a system that facilitates access of farmers or their organizations to new knowledge, information and technologies and promotes interaction with research, education, agri‐business, and other relevant institutions to assist them in developing their own technical, organizational and management skills and practices. It can interpret and explain the language of modern technology to farmers, fi shers and ranchers (Suvedi and Kaplowitz, 2016). Various forms of agricultural extension services exist throughout the world. Their primary functions have been to facilitate learning and extend new knowledge and technologies in non-formal educational settings to improve agricultural productivity and increase farmers’ incomes. The nomenclature of extension service providers varies by country. The frontline workers are known as agricultural extension workers, agricultural extension offi cers, extension educators, livestock development offi cers, fi shery technicians, and community forestry and/or natural resources management officers.